2020
DOI: 10.1371/journal.pone.0228258
|View full text |Cite
|
Sign up to set email alerts
|

Anemia, micronutrient deficiencies, malaria, hemoglobinopathies and malnutrition in young children and non-pregnant women in Ghana: Findings from a national survey

Abstract: Nationally representative data on the micronutrient status of Ghanaian women and children are very scarce. We aimed to document the current national prevalence of micronutrient deficiencies, anemia, malaria, inflammation, α-thalassemia, sickle cell disease and trait, and under-and over-nutrition in Ghana. In 2017, a two-stage cross-sectional design was applied to enroll preschool children (6-59 months) and non-pregnant women (15-49 years) from three strata in Ghana: Northern, Middle and Southern Belt. Househol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 31 publications
5
45
3
1
Order By: Relevance
“…To account for Ghana's administrative, agroecological and population density zoning, the following zones were considered as separate explicit strata: (1) Southern Belt, consisting predominantly of coastal savannah and rainforest and comprising the Greater Accra, Central, Volta and Western regions; (2) Middle Belt, consisting predominantly of deciduous forest and comprising the Brong‐Ahafo, Ashanti and Eastern regions; and (3) Northern Belt, consisting predominantly of Guinean/Sudanian savannah and comprising the Northern, Upper West and Upper East regions. Sample size calculation is described elsewhere (Wegmüller et al, 2020). A two‐stage sampling procedure with selection of census enumeration areas (EAs) in the first stage with probability of selection being proportional to size was used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To account for Ghana's administrative, agroecological and population density zoning, the following zones were considered as separate explicit strata: (1) Southern Belt, consisting predominantly of coastal savannah and rainforest and comprising the Greater Accra, Central, Volta and Western regions; (2) Middle Belt, consisting predominantly of deciduous forest and comprising the Brong‐Ahafo, Ashanti and Eastern regions; and (3) Northern Belt, consisting predominantly of Guinean/Sudanian savannah and comprising the Northern, Upper West and Upper East regions. Sample size calculation is described elsewhere (Wegmüller et al, 2020). A two‐stage sampling procedure with selection of census enumeration areas (EAs) in the first stage with probability of selection being proportional to size was used.…”
Section: Methodsmentioning
confidence: 99%
“…To account for Ghana's administrative, agroecological and population density zoning, the following zones were considered as separate explicit strata: (1) Southern Belt, consisting predominantly of coastal West and Upper East regions. Sample size calculation is described elsewhere (Wegmüller et al, 2020). A two-stage sampling procedure with selection of census enumeration areas (EAs) in the first stage with probability of selection being proportional to size was used.…”
Section: Survey Design and Participantsmentioning
confidence: 99%
“…The prevalence of anaemia among women is high in Ghana [19]. In the Ashanti region, more than half of women are anaemic [20].…”
Section: Introductionmentioning
confidence: 99%
“…Mothers' occupation and location have been linked respectively with high malaria parasitaemia and clinical severity among children [45,46]. Several other studies have also shown an association between income and child health, suggesting that low-income families are less likely to seek prompt treatment for their sick children [47].…”
Section: Discussionmentioning
confidence: 99%